Capturing Morphophonemic Processes in the Short Movie Entitled “Fool’s Day” - Rahardi, Panggih (Universitas Nurul Jadid, 2023)
A movie is a form of literature that contains linguistic features in its script. The script of a movie uttered by the actors has many interesting linguistic aspects that can be studied. Hence, this study aims to identify the morphophonemic processes in the movie